2010
DOI: 10.1007/s11664-010-1314-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Rate on Microstructural Homogeneity and Grain Size of n-Type Si-Ge Thermoelectric Alloy by Melt Spinning

Abstract: n-Type Si-Ge thermoelectric alloys were prepared using a melt spinning (MS) process, and then the microstructures of the samples were investigated. The alloys studied were ribbon shaped with a thickness of about 30 lm. Scanning electron microscopy (SEM) along with energy-dispersive spectrometry (EDS) and x-ray diffraction (XRD) showed a predictable, homogeneous, fine-grained microstructure at the high cooling rate, different from those of samples created by slow solidification (SS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Contrary to the authors' expectations, the degree of segregation and heterogeneity increased with the increasing cooling rate, and compound-like regions with preferred stoichiometries were observed in Ge-rich grain-boundary regions. The observation of stoichiometric compositions at grain boundaries agreed with previous works on SiGe alloys prepared by melt spinning [15]. Moreover, other authors [21,22] observed preferred stoichiometries in ball-milled SiGe powders.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to the authors' expectations, the degree of segregation and heterogeneity increased with the increasing cooling rate, and compound-like regions with preferred stoichiometries were observed in Ge-rich grain-boundary regions. The observation of stoichiometric compositions at grain boundaries agreed with previous works on SiGe alloys prepared by melt spinning [15]. Moreover, other authors [21,22] observed preferred stoichiometries in ball-milled SiGe powders.…”
Section: Introductionsupporting
confidence: 90%
“…Previous studies have shown that homogeneous melts can be produced by rapid cooling during microgravity processing, with the absence of thermal convection and density-based segregation enabling the formation of more compositionally uniform structurer [14]. Zhang, et al [15] used melt spinning to investigate the effect of cooling rate (>10 5 K s − 1 ) on the microstructure of n-type SiGe alloys. The results of energy-dispersive X-ray spectroscopy (EDX) point measurements suggested that inhomogeneity was caused by near-equilibrium solidification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, careful observation of previously published micrographs, e.g. Figure 3 in Zhang et al [11], show identical features, although the original authors appear not to have commented upon these features. In fact, TEM and EBSD analysis reveal that these Ge-rich regions are generally part of one of the Si-rich grains to which they are attached, rather than being separate crystallites.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, the microstructure of the rapidly solidified samples displayed greater homogeneity with less segregation, which was attributed to solute trapping. In relation to the cooling rate Zhang et al also found that the grain size decreased with an increasing cooling rate [11].…”
Section: Introductionmentioning
confidence: 94%